Planned drug holidays during treatment with lenvatinib for radioiodine-refractory differentiated thyroid cancer: a retrospective study - Matsuyama, Chihiro; Enokida, Tomohiro; Ueda, Yuri; Suzuki, Shinya; Fujisawa, Takao; Ito, Kazue; Okano, Susumu; Tahara, Makoto (Frontiers in Oncology, 2023)
Background: In the phase 3 SELECT study, lenvatinib significantly improved prognostic outcomes vs. placebo in patients with radioiodine-refractory differentiated thyroid cancer (RR-DTC). However, toxicity of lenvatinib is sometimes considerable and requires frequent dose interruptions and modifications. Recently, planned drug holidays have been proposed as a means of avoiding severe adverse events (AEs).Methods: We retrospectively reviewed medical records to compare the efficacy and safety of lenvatinib in RR-DTC patients who underwent planned drug holidays (planned holiday group) vs. those who received conventional daily oral administration (daily group).Results: The subjects were 25 patients in the planned holiday group and 21 in the daily group. Median age was 73 years (range 43-84) and 62 years (range 42-75), and histologic subtype of papillary/follicular was 21/4 cases and 15/6 cases, respectively. Time to treatment failure (TTF) and overall survival (OS) were significantly longer in the planned holiday group than the daily group (not reached [NR] vs. 14.9 months, hazard ratio [HR] 0.25, 95% confidence interval [Cl] 0.11-0.58, p<0.001; NR vs. 26.6 months, HR 0.20, 95% CI 0.073-0.58, p=0.001, respectively). Median progression-free survival (PFS) was NR in the planned holiday group vs. 15.1 months in the daily group (HR 0.31, 95% CI 0.14-0.68, p=0.002). Duration of the period with lenvatinib dose ≥10 mg was significantly longer in the planned holiday group (NR vs. 6.5 months, HR 0.22, 95% CI 0.10-0.49, p<0.001), and the frequency of drug interruption due to intolerable AEs was lower (68.0% vs. 95.2%, p=0.027).Planned drug holidays for lenvatinib demonstrated significantly longer PFS, TTF, and OS than daily oral administration, and less intolerable toxicity leading to further unplanned treatment interruption.These benefits were apparently associated with a more extended period of lenvatinib administration at ≥10 mg.These findings might contribute to a favorable patient prognosis and safer toxicity profile.